2005
DOI: 10.1007/s00531-005-0015-0
|View full text |Cite
|
Sign up to set email alerts
|

The significance of fixed ammonium in Palaeozoic sediments for the generation of nitrogen-rich natural gases in the North German Basin

Abstract: In contrast to predominantly hydrocarbon-rich natural gases in the western part of the Central European Basin (CEB), accumulations of natural gases from the eastern part of the North German Basin (NGB) are nitrogen-rich with up to 90% N 2 . This study is focused on the behaviour of fixed ammonium in clay minerals of organic-rich Palaeozoic sediments in the eastern part of the NGB as a major source of nitrogen-rich natural gases. Carboniferous shales have been investigated for a better understanding of nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 72 publications
(37 citation statements)
references
References 35 publications
(54 reference statements)
0
36
0
Order By: Relevance
“…Although nitrogen release under upper-diagenetic conditions cannot be excluded, Mingram et al 2005 (this issue) have shown, for example, the potential for ammonium fixation in Namurian shales increases with increasing thermal maturity up to low-metamorphic conditions. On the other hand, strongly altered samples from a drill core from the central part of the NGB show a significant decrease of ammonium down to 500 ppm coupled with a shift in d 15 N from +3 up to +6 & which suggests a release of nitrogen on a large scale (Mingram et al 2005). WRI of brines with shales is also indicated by the sulfur isotopic composition of anhydrites in fissures hosted by Namurian shales.…”
Section: Origin Of Nitrogenmentioning
confidence: 96%
See 1 more Smart Citation
“…Although nitrogen release under upper-diagenetic conditions cannot be excluded, Mingram et al 2005 (this issue) have shown, for example, the potential for ammonium fixation in Namurian shales increases with increasing thermal maturity up to low-metamorphic conditions. On the other hand, strongly altered samples from a drill core from the central part of the NGB show a significant decrease of ammonium down to 500 ppm coupled with a shift in d 15 N from +3 up to +6 & which suggests a release of nitrogen on a large scale (Mingram et al 2005). WRI of brines with shales is also indicated by the sulfur isotopic composition of anhydrites in fissures hosted by Namurian shales.…”
Section: Origin Of Nitrogenmentioning
confidence: 96%
“…The origin of nitrogen in gas reservoirs in the eastern part of the NGB is controversial (for references see Mingram et al 2005). Chemical analysis of individual fluid inclusions hosted in a fissure calcite sample from the Schwerin 1 borehole (Table. 1, 2) proves that there to be a strong evidence for local interactions of saline brines with Permian volcanic rocks and a probable release of nitrogen from feldspar and/or mica.…”
Section: Origin Of Nitrogenmentioning
confidence: 99%
“…The notably high H 2 concentration (5.64%) in the P6 sample (Table 4) is attributed to recent microbial processes because this sample was collected from a small gas, oil and brine show. Nitrogen is produced in great quantities during the thermogenic transformation of organic matter both from humic and sapropelic organic matter (Maksimov et al, 1982;Kotarba, 1988;Krooss et al, 1995;Littke et al, 1995) or from NH 4 -rich illites that had undergone intensive fluid/rock interaction Mingram et al, 2005). The process of molecular nitrogen (N 2 ) production from organic matter was also documented by pyrolysis experiments (Gerling et al, 1997).…”
Section: Gas Molecular Compositionmentioning
confidence: 92%
“…Basinal shaly sediments of early Namurian age can have TOC contents between 0.2 wt% and 8 wt% (well Schwalmtal 1, well Münsterland 1). Maturities of Namurian A sediments differ strongly between 3.3% VR r (well Brakel 1; Teichmüller et al, 1979), through 3.5% VR r (well Schwalmtal 1; Krooss et al, 2005) and 4.6% VR r (well Pröttlin; Mingram et al, 2005), to 5-6% VR r (well Münsterland 1; Teichmüller et al, 1979). In terms of shale gas prospectivity, Namurian A sediments are too mature across large areas.…”
Section: R Littke Et Al / Unconventional Gas Resources In the Paleozmentioning
confidence: 99%